Bacteriology of diabetic foot ulcers and their antibiotic resistance ability - Baral, Poulomi; Afnan, Nafisa; Akter, Baby; Prapti, Shek Rabia (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology 2022.